Islamic Education Curriculum - Ahmad Sahira Zandi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Islamic Education Curriculum is an important aspect in achieving the goals of Islamic Education, like a heart in the human body, if the heart is healthy, the body will feel healthy, the curriculum is good, the material will be delivered well, the success or failure of an Education goal will certainly depend on the curriculum used, the Curriculum as an Education design has a central role in the realization of Islamic Education, and determines the implementation process and results of Education, so what is meant by the Islamic Religious Education curriculum is a conscious and planned effort in preparing students to know, understand, appreciate, believe in and practice the teachings of Islam as a whole, the Islamic Education Curriculum must also be appropriate and directed at students in stages, for example, the adjustment of the Islamic Religious Education curriculum for children is certainly different from the Islamic Religious Education curriculum for adolescents.